Stability strengths and weaknesses in protein structures detected by statistical potentials: Application to bovine seminal ribonuclease. Issue 1 (9th December 2015) - De Laet, Marie; Gilis, Dimitri; Rooman, Marianne
ABSTRACT: We present an in silico method to estimate the contribution of each residue in a protein to its overall stability using three database‐derived statistical potentials that are based on inter‐residue distances, backbone torsion angles and solvent accessibility, respectively. Residues that contribute very unfavorably to the folding free energy are defined as stability weaknesses, whereas residues that show a highly stabilizing contribution are called stability strengths. Strengths and/or weaknesses on residues that are in spatial contact are clustered into 3‐dimensional (3D) stability patches. The identification and analysis of strength‐ and weakness‐containing regions in a protein may reveal structural or functional characteristics, and/or interesting spots to introduce mutations. To illustrate the power of our method, we apply it to bovine seminal ribonuclease. This enzyme catalyzes the degradation of RNA strands, and has the peculiarity of undergoing 3D domain swapping in physiological conditions. The weaknesses and strengths were compared among the monomeric, dimeric and swapped dimeric forms. We identified weaknesses among the catalytic residues and a mixture of weaknesses and strengths among the substrate‐binding residues in the three forms. In the regions involved in 3D swapping, we observed an accumulation of weaknesses in the monomer, which disappear in the dimer and especially in the swapped dimer. Moreover, monomeric homologous proteins were found to exhibit less weaknesses in these regions, whereas mutants known to favor unswapped dimerization appear stabilized in this form. Our method has several perspectives for functional annotation, rational prediction of targeted mutations, and mapping of stability changes upon conformational rearrangements. Proteins 2016; 84:143–158. © 2015 Wiley Periodicals, Inc.